The Lees of Virginia : seven generations of an American family - Nagel, Paul C. (Oxford University Press, 1990)
In The Lees of Virginia, Paul Nagel chronicles seven generations of Lees, from the family founder Richard to General Robert E. Lee, covering over two hundred years of American history. We meet Thomas Lee, who dreamed of America as a continental empire. His daughter was Hannah Lee Corbin, a non-conformist in lifestyle and religion, while his son, Richard Henry Lee, was a tempestuous figure who wore black silk over a disfigured hand when he made the motion in Congress for Independence. Another of Thomas' sons, Arthur Lee, created a political storm by his accusations against Benjamin Franklin. Ar.